PENERAPAN EVIDENCE BASED NURSING EFEKTIVITAS PELATIHAN KOMUNIKASI TERAPEUTIK GUNA MENINGKATKAN PENGETAHUAN DAN CARING PERAWAT DI IGD RUMAH SAKIT BHAYANGKARA TK. I RADEN SAID SUKANTO - Ahmad Nursalam, (2023)
This therapeutic relationship is established through therapeutic communication, which is used to ensure the effectiveness of the therapy program. Caring behavior is the basis of a helping relationship between nurse and patient. However, there are still many nurses who do not use therapeutic communication when interacting with patients. So it is necessary to have training related to therapeutic communication training so that nurses can recall the principles and how to carry out therapeutic communication. The application of evidence based nursing was carried out on 13 nurses in the emergency room at Bhayangkara Hospital TK.I Raden Said Sukanto. Therapeutic communication training was conducted for 3 consecutive days with 7 participants on the first day, 6 participants on the second day, and 6 participants on the third day. The results of the pretest and posttest showed that before being given therapeutic communication training the average value of the nurse's knowledge was 10.00 while after being given it increased to 11.77. The results of the paired t-test showed a p-value of 0.000 which means that therapeutic communication training has a significant effect on nurses' knowledge. The results of the nurse caring evaluation showed that the majority of nurses had a good caring attitude with 9 (69.2%) nurses, while the other 4 (30.8%) nurses did not yet have a good caring attitude. Therapeutic communication must be carried out by all nurses in order to create comprehensive and efficient nursing services so as to increase patient satisfaction.